Design and simulation of microstrip phased array antenna for 2.0–2.8 GHz - Handayani, Kurnia Wati Pascitra; Soim, Sopian; Anugraha, Nurhajar (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to create and test a microstrip array antenna with eight elements that works in the 2.0–2.8 GHz frequency range. We use CST Studio Suite to run simulations that check performance metrics like return loss (S11), VSWR, gain, and radiation pattern. The results show that the antenna has a return loss of -24 dB and a VSWR of 1.13 at a frequency of 2.4 GHz, which means the impedance is very well matched. However, the radiation and total efficiencies at 2 GHz and 2.8 GHz are still low, so the design can't handle the highest frequencies in the working range. The 126 MHz bandwidth should be able to cover channels 1 to 13 in Band 40 (2300–2400 MHz), but the antenna needs to work better at frequencies above 2.4 GHz to be helpful for all applications. Compared to other studies, this antenna's gain and efficiency are still not as good as those of other phased array antennas. This study is the first step towards creating a possible digital beam steering system that adaptively aligns signals to user movement to reduce interference in mobile environments.